Educational and Lingusitic Problems of the Idigenous Peoples of Venezuela - Bondarenko Pisemskaya, Natalia (Íkala, Revista de Lenguaje y Cultura, 2009)
<!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> In this paper, we examine the situation of Venezuelan indigenous peoples and their respective languages. We present the history and scope of the System of Intercultural Bilingual Education and discuss the implications of language policies of the Venezuelan State regarding linguistic and educational matters. It is a documentary study conducted using qualitative methods, theoretical analysis, and a semi-structured, focused interview. We conclude that, despite the efforts of the Venezuelan State, the indigenous peoples themselves must take responsibility for both their destiny and their languages, guided by the principle of self-determination, without so much intervention by the State. Received: 18-11-08 /Accepted: 11-07-09 How to reference this article: Bondarenko Pisemskaya, N. (2009). Problemática lingüístico-educativa de los pueblos indígenas de Venezuela. Íkala. 14(3), pp.65-84.